Protein profile of dairy products: Simultaneous quantification of twenty bovine milk proteins. (October 2019) - Bär, Cornelia; Mathis, Déborah; Neuhaus, Patrick; Dürr, Desirée; Bisig, Walter; Egger, Lotti; Portmann, Reto
Abstract: While proteomic techniques allow the identification and relative quantification of thousands of proteins in a single run, methods for absolute quantification remain laborious. In this study, a newly developed multiple reaction monitoring (MRM) method using liquid chromatography mass spectrometry (LC-MS) that enables the simultaneous quantification of twenty key milk proteins is presented. The selected proteins comprise all individual caseins, the major whey proteins and most well-known milk fat globule membrane (MFGM) proteins. For validation, the twenty milk proteins in raw milk, raw cream, raw milk Emmental cheese and whey, were quantified as well as in eighteen commercial heat-treated dairy products. The method presented is ideally suited for various applications, for example, the comparison of the protein patterns in raw milk of cows at different stages of lactation or of different breeds.